Biosynthesis of ilamycins featuring unusual building blocks and engineered production of enhanced anti-tuberculosis agents - Junying Ma (Nature Portfolio, 2017)
Tuberculosis (TB) remains one of the world’s deadliest communicable diseases, novel anti-TB agents are urgently needed due to severe drug resistance and the co-epidemic of TB/HIV. Here, the authors show that anti-mycobacterial ilamycin congeners bearing unusual structural units possess extremely potent anti-tuberculosis activities.